An overview of regulations, guidelines, and intervention strategies for Listeria monocytogenes in ready-to-eat meat and poultry products - Bangel, Natasha Ann (Kansas State University, 2011)
Listeria monocytogenes has the potential to contaminate ready-to-eat (RTE) meat and poultry products. Listeria monocytogenes contamination is a hazard that can potentially occur after post-lethality treatment in a processing environment during slicing or packaging of RTE meat products. United States Department of Agriculture’s Food Safety and Inspection Service (USDA/FSIS) requires facilities to have intervention strategies to demonstrate control of this pathogen in RTE meat and poultry products. FSIS categorizes different intervention strategies into Alternative 1, 2, or 3. If an establishment chooses Alternative 1, it must use a post-lethality treatment that reduces or eliminates microorganisms on the product and an antimicrobial agent or process that suppresses or limits the growth of L. monocytogenes. If an establishment chooses Alternative 2, it can either use a post-lethality treatment or an antimicrobial agent or process that suppresses or limits growth of L. monocytogenes. Under Alternative 3, the establishment must have a detailed sanitation program as its intervention strategy. As establishments increase the number of interventions or change from Alternative 3 to 2 to 1, the frequency of FSIS sampling of RTE meat and poultry products for safety and wholesomeness decreases. The effectiveness of post-package decontamination technologies such as high-pressure processing, ultraviolet C light, and pre/post-package surface pasteurization have been researched for controlling L. monocytogenes in RTE products. Formulating meat products with antimicrobial additives such as lactates, sodium lactate and sodium diacetate, potassium lactate and sodium diacetate, sodium levulinate, lauric arginate, glucono-delta-lactone, or organic acids is another common approach to control L. monocytogenes in RTE meat products. Also, a combination of sodium lactate and sodium diacetate in a formulation is an acceptable antimicrobial strategy to provide Alternative 2 status. Bacteriocins such as nisin can also be added to the formulation of RTE meat and poultry products for controlling L. monocytogenes. In addition nisin can be applied as packaging film coating. Another approach for controlling L. monocytogenes in products such as jerky, kippered steaks, snack sticks and turkey tenders is the use of packaging environments and holding times prior to shipping. In conclusion, there are various approaches for controlling L. monocytogenes in RTE meat and poultry products post-lethality and processors should consider these options rather than relying on sanitation alone.
Keywords: Ready-to-eat (RTE); Meat; Antimicrobials; Listeria monocytogenes; Poultry; Alternative; Food Science (0359)